2022
DOI: 10.1002/saj2.20391
|View full text |Cite
|
Sign up to set email alerts
|

A Freundlich‐type multi‐component approach for modeling the sorption of nickel and phosphate in soil

Abstract: In this study, the effect of phosphate on Ni sorption by Mahan soil was investigated. In batch experiments, an initial solution concentration of 1 mM phosphate increased Ni sorption by 15.1%, and initial concentrations of 1 mM Ni increased phosphate sorption by 12.8%. The effect of phosphate on Ni sorption, and vice versa, was dependent on initial concentrations of either solute, with greater effects being observed with greater initial concentrations. Sequential extractions suggest that the increased sorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 88 publications
0
15
0
Order By: Relevance
“…• 2015: Hamidouche et al 35 proved Brouers' result and have shown how the Freundlich formula can be derived from the hypergeometric function by approximation. • 2022: Padilla et al 36…”
Section: ■ Timeline Of the Freundlich Isothermmentioning
confidence: 99%
See 4 more Smart Citations
“…• 2015: Hamidouche et al 35 proved Brouers' result and have shown how the Freundlich formula can be derived from the hypergeometric function by approximation. • 2022: Padilla et al 36…”
Section: ■ Timeline Of the Freundlich Isothermmentioning
confidence: 99%
“…An important specific type of multicomponent competitive system arises when a (divalent) metal cation Me and an (in)organic ligand L can be simultaneously fixed at the surface S of a soil sample (note that the ionic charges were omitted for the sake of simplicity). For such a case, commonly encountered at metalcontaminated sites, Padilla et al 36 developed a phenomenological Freundlich-type isotherm model based on the surfacecomplexation model (SCM). 41 Several surface interactions can thus be described as binary (S−Me and S−L) and ternary (S− Me−L (type-A complex) and S−L−Me (type-B Each binary complex can be described on the basis of a Freundlich-type relationship, such as, for the binary complexes:…”
Section: Proposed a Phenomenologicalmentioning
confidence: 99%
See 3 more Smart Citations